Geopolitical and Economic Aspects of Development of the Independent States of the Eurasian Region in the Context of the Eurasian Integration (1991-2013) - Vladimir Evgenyevich Frolov (Управленческое консультирование)
This article is devoted to the study of the process of solution by the Eurasian countries of the systemic crisis, caused by the collapse of the Soviet Union, in the context of processes of Eurasian integration.